2018
DOI: 10.1002/er.4269
|View full text |Cite
|
Sign up to set email alerts
|

Technical and economic comparison of grid supportive vanadium redox flow batteries for primary control reserve and community electricity storage in Germany

Abstract: Summary Primary control reserve and maximising self‐consumption are currently two of the main applications for large‐scale battery storage systems. Although being currently the most profitable application for large‐scale batteries in Germany, storage systems applying primary control reserve have not been implemented in a grid supportive manner in distribution grids yet. Despite a current unfavourable regulatory framework and reimbursement scheme for community electricity storages in Germany, they are potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…For the grid losses, 64 EUR/MWh are agreed with the DSO of the pilot region. The cost for the additional energy required to provide reactive power control is set to 56 EUR/MWh for the large scale BSS [15].…”
Section: B Economic Comparison Of the Flexibility Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the grid losses, 64 EUR/MWh are agreed with the DSO of the pilot region. The cost for the additional energy required to provide reactive power control is set to 56 EUR/MWh for the large scale BSS [15].…”
Section: B Economic Comparison Of the Flexibility Optionsmentioning
confidence: 99%
“…This study is based on an extensive review of operation strategies for PCR and self-consumption maximisation of the same authors [2], [13], [14]. Derived from these reviews, the two technically and economically most promising system/ grid supportive operation strategies for PCR and CES were applied and analysed for the VRFB prototype [15]. In this paper, the impact of these two operation strategies on distribution grid planning are compared along with cosϕ(P)-control and Q(V)control of PV systems and RES.…”
Section: Introductionmentioning
confidence: 99%
“…[13] presents an analysis of operating central storage units directly connected to mediumvoltage grids to provide power system services. [14] compares the technical service provision to self-consumption maximization service using a centralised battery at distribution level. However, [13], [14] do not consider distributed batteries at prosumer level which can change their operation with an economic incentive mechanism.…”
Section: B Aggregated Flexibility Servicesmentioning
confidence: 99%
“…Techno-economic feasibility models have been recently reviewed [40]; most of them centre on capital cost, stressing the significant role of vanadium reactants, and revealing wide variability in the assumed prices of membranes and ancillary equipment. Recently, two models for grid-level energy storage, one in Germany [41], and the other in the USA [42], concluded that RFB investment costs should be reduced by 20-30%, in order to remain competitive. Notably, a model for the implementation of large-area electrodes has estimated potential cost reductions of about 25% [43], while new models could establish up-to-date cost and financing targets by taking into account new electrolyte leasing schemes [6].…”
Section: Mathematical Modellingmentioning
confidence: 99%